2009
DOI: 10.1017/s1466252309990016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic factors affecting the inflammatory response of periparturient dairy cows

Abstract: Dairy cattle are susceptible to increased incidence and severity of disease during the periparturient period. Increased health disorders have been associated with alterations in bovine immune mechanisms. Many different aspects of the bovine immune system change during the periparturient period, but uncontrolled inflammation is a dominant factor in several economically important disorders such as metritis and mastitis. In human medicine, the metabolic syndrome is known to trigger several key events that can ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
215
1
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(237 citation statements)
references
References 80 publications
(126 reference statements)
7
215
1
10
Order By: Relevance
“…Negative correlation between vitamin C with milk parameters might point to the increase of oxidative processes in high-yielding dairy cows (Sordillo et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative correlation between vitamin C with milk parameters might point to the increase of oxidative processes in high-yielding dairy cows (Sordillo et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Some earlier studies showed relationships between milk yield with level of cholesterol and vitamin C in milk and blood (Ling et al, 2003;Chládek et al, 2004;Sordillo et al, 2009;Strzałkowska et al, 2009a, b). However, information about associations between biochemical parameters in blood and milking traits of dairy cows with different level of productivity is still not complete.…”
mentioning
confidence: 96%
“…Some researchers demonstrated that elevated NEFA concentrations present positive risk factors for many proinflammatory diseases in dairy cows [5,10,25]. Also, during the transition period when NEFA concentration increase, dairy cows experience immune dysfunction that enhances their susceptibility to disease [3,11,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Also, during the transition period when NEFA concentration increase, dairy cows experience immune dysfunction that enhances their susceptibility to disease [3,11,23,25]. This suggests that perhaps inflammation underlies metabolic disturbances in obese dairy cows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation